2013
DOI: 10.1007/s12013-013-9516-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-19b Overexpression on Proliferation, Differentiation, Apoptosis and Wnt/β-Catenin Signaling Pathway in P19 Cell Model of Cardiac Differentiation In Vitro

Abstract: MicroRNA (miR)-19b is part of the miR-17-92 cluster associated with cardiac development. Here, we investigated the effects of overexpressing miR-19b on proliferation, differentiation, apoptosis, and regulation of the Wnt/β-catenin signaling pathway in the multipotent murine P19 cell line that can be induced to undergo cardiogenesis. P19 cells were transfected with the miR-19b plasmid or empty vector, and miR-19b overexpression was verified by Quantitative Real-Time PCR (qPCR). The miR-19b or vector control sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…MiR 19b-3p expression could inhibit TF expression, which suggests that TF may be a target gene of miR-19b-3p. In another study, Qin et al (2013) found that miR-19b-3p may be associated with the Wnt signalling pathway in cardiac development but without showing the direct target genes. In the current study, STAT3 activation was negatively regulated by miR-19b-3p and miR-29c-3p in SH-SY5Y cells, suggesting that STAT3 may be a direct target gene of these miRNAs.…”
Section: Discussionmentioning
confidence: 97%
“…MiR 19b-3p expression could inhibit TF expression, which suggests that TF may be a target gene of miR-19b-3p. In another study, Qin et al (2013) found that miR-19b-3p may be associated with the Wnt signalling pathway in cardiac development but without showing the direct target genes. In the current study, STAT3 activation was negatively regulated by miR-19b-3p and miR-29c-3p in SH-SY5Y cells, suggesting that STAT3 may be a direct target gene of these miRNAs.…”
Section: Discussionmentioning
confidence: 97%
“…miRNAs are important regulators of cardiovascular development, and dysregulation of their expression has been linked to cardiac diseases [245247]. miR-19b overexpression study revealed its regulation of the left-right symmetry and cardiac development in zebrafish embryo by directly suppressing β - catenin ( CTNNB1 ) of the Wnt signaling pathway [248,249]. The deformed cardiac phenotype was partially rescued by lithium chloride treatment which inhibits GSK3β, leading to an accumulation of β-catenin [248].…”
Section: Microrna Regulation Of Wnt Signaling Pathways In the Contmentioning
confidence: 99%
“…Considering that AMI is a complex pathophysiological process with the involvement of various kinds of cells, the contribution of non cardiac-enriched miRNAs is worthy of equal attention. miR-19b is a member of the miR-17-92 cluster (miR-17/18a/19a/19b/20a/92a), which is located on chromosome 13 [22,23]. Previous studies have shown that miR-19b is involved in aging-associated heart failure and the positive regulation of cardiomyocyte hypertrophy and apoptosis by targeting atrogin-1 and MuRF-1 [24].…”
Section: Introductionmentioning
confidence: 99%